New efficient fractal models for MapReduce in OpenMP parallel environment - Muslim Mohsin Khudhair; Furkan Rabee; Adil AL_Rammahi (Institute of Advanced Engineering and Science, 2023)
Parallel data processing is one of the specific infrastructure applications categorized as a service provided by cloud computing. In cloud computing environments, data-intensive applications increasingly use the parallel processing paradigm known as MapReduce. MapReduce is based on a strategy called